The Effectiveness of The Ombudsman Republic of Indonesia Representative of Bengkulu in Handling and Resolving Public Complaints - Ayu Cantika, Suci; Suratman, Suratman; Yogopriyatno, Jatmiko (Future Science, 2024)
The Ombudsman of the Republic of Indonesia (ORI) Representative of Bengkulu has experienced a significant increase in public complaints over the past five years while facing challenges such as limited human resources and a large working area. This study aims to evaluate the effectiveness of the Bengkulu Representative Ombudsman in handling and resolving public complaints. A descriptive qualitative approach was employed, utilizing semi-structured interviews, non-participant observation, and document analysis for data collection. Data analysis followed the Miles and Huberman approach. Results indicate that ORI Bengkulu Representative demonstrates effectiveness in four key areas: adaptation (through rigorous recruitment and comprehensive activities), integration (via external cooperation and effective communication), motivation (evidenced by employee engagement and adequate facilities), and production (reflected in improved complaint handling and public service compliance scores). Despite these positive outcomes, the office continues to grapple with resource limitations and the extensive geographical coverage of its jurisdiction. In conclusion, while the ORI Bengkulu Representative exhibits good overall effectiveness, there remains a need for capacity building to further enhance its role in monitoring and improving public service quality in Bengkulu Province. This study contributes to the understanding of ombudsman effectiveness in regional contexts and highlights areas for potential improvement in public service oversight.